Self-fashioning and the intersectional self: Teresa de Cartagena by Teresa de Cartagena - Conde, J-C (De Gruyter, 2021)
This article examines the way in which Teresa de Cartagena builds and presents her literary self in her literary works, Arboleda de los enfermos and Admiración operum Dei. The examination of this literary self-fashioning (a concept based, but different from, the one coined under the same denomination by Stephen Greenblatt) of Teresa de Cartagena is conducted under the theoretical framework of intersectionality, which allows to see the multi-layered and dynamic complex nature of this author’s literary self, and the implications this has for the understanding of her work.